Growth analysis, micro-climatic parameters and productivity of wheat (Triticum aestivum L.) in relation to hydrogel under different irrigation regimes and nutrient levels - Dar, Shahid B; Ram, Hari (Journal of Cereal Research, 2016)
Wheat (Triticum aestivum L.) is the world’s most widely cultivated food crop. Besides staple food for human beings, wheat straw also serves as good source of feed for animals (Sarwaret al., 2006). Wheat grain contains about 12% protein which is more than that in other cereals and is of special significance to maintain the good bread making quality due to the presence of a characteristic substance called ‘gluten’. Water availability is one of the most important factors influencing the growth and productivity of wheat. Water requirement of wheat vary from 180-420 mm depending upon the duration of the crop. Thus, there is a sufficient scope to carry out what minimum amount of water should be applied to have maximum yield per unit of water applied.